The Impact of Online Promotion on Increasing Product Sales of SME - Daeli, Komiteriang; Bate’e, Maria Magdalena; Zalukhu, Yuterli; Mendrofa, Yupiter (Manunggal Halim Jaya, 2024)
This thesis discusses the influence of online promotion on increasing sales of SME products in Lahomi District, West Nias Regency. This study aims to determine the influence of online promotion on increasing sales of SME products in Lahomi District, West Nias Regency. This study uses a quantitative research method with a data collection technique using a questionnaire. Based on the results of the T-Test where the sign value of the X variable is known 001> 0.05 and the t-value is 6.841 <2.054 so it can be concluded that Ha is accepted and has an effect on the Sales Increase variable (Y). Based on the determination coefficienT-Test, the results obtained are that the Adjuster R-Square value is 0.589, this means that the Promotion Variable (X) is able to explain the increase in sales (Y) of 0.589 with a percentage of 58.9% after being adjusted for the sample and independent variables while the remaining 41.1% is explained by other variables outside this study.